NILAI-NILAI ISLAMI DALAM NOVEL ASSALAMUALAIKUM BEIJING KARYA ASMA NADIA - Andriani, Susi; Hayati, Yenni; Nst., Muhammad Ismail (Jurnal Bahasa dan Sastra, 2018)
This study aims to describe and explain the value of aqidah, syariah values, and moral values depicted in the speech of a character or character behavior in the novel Assalamualaikum Beijing by Asma Nadia. This research type is qualitative research with descriptive method. Data collection is done through (1) reading and marking the events and speeches of characters or characters in the novel Assalamualaikum Beijing by Asma Nadia, in order to get a clear picture of the content of the novel to be studied; (2) marking the novel part that will be the focus of research that is the value of aqidah, syariah value, and moral value; (3) to record data on Islamic values contained in the novel by looking at issues that appear through the speech of a character or behavior of a story character in a data recording format; (4) inventory data using data inventory format. Based on the results of the study concluded, the following points. The Islamic values in Asma Nadia's novel Assalamualaikum Beijing are (1) the value of faith that can be seen from the actions and behaviors of the character: faith in God, faith in God's book, faith in the last day, and faith in Qada and Qadar (destiny); (2) the value of sharia is like the sentence shahada, pray, pray, dzikir, dress, and marriage; (3) moral values such as morality to God that is grateful and morals towards each other is divided into (a) morals to the self that is patient, sincere, and self-guard; (b) morals to the family that is doing good to the parents, and educating children; (c) morals to others is to say hello.Keywords: islamic values, Assalamualaikum Beijing